A COMPREHENSIVE SURVEY ON MASTITIS: DETECTION TECHNIQUES, INFRARED THERMOGRAPHY, AND STRATEGIES FOR SUBCLINICAL MASTITIS PREVENTION - M. Chengathir Selvi; M. Swarnaa; S.T. Veena; K. Kanagarajadurai (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Mastitis, a prevalent inflammatory condition in the mammary gland of dairy cattle, is primarily caused by bacterial infections and results in reduced milk   production and quality. There are two main types of mastitis: clinical and subclinical. Clinical mastitis is visible through symptoms such as swelling, redness, and abnormal milk secretion, while subclinical mastitis lacks visible signs but still impacts milk production and quality. The economic and health impacts of mastitis in cattle are profound, leading to reduced milk yield, increased veterinary costs, and potential culling of affected animals, contributing to substantial financial losses in the dairy industry. Traditionally, mastitis has been detected through clinical observation, somatic cell count (SCC) analysis, and microbiological tests. However, early detection, especially of subclinical cases, remains challenging. Infrared thermography (IRT) has emerged as a promising, non-invasive tool for early mastitis detection by capturing temperature variations in the udder caused by inflammation. IRT enables the identification of heat patterns associated with infections before clinical signs are visible. This study investigates the potential of IRT as a reliable and cost-effective method for early detection of mastitis in cattle, contributing to  improved  animal  health  and  reduced  economic  losses  for  dairy  farmers